PENERAPAN METODE PROBLEM SOLVING DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR SISWA SEKOLAH DASAR - Sri Wahyuni Repelitawati (Universitas Tribhuwana Tunggadewi, 2022)
The purpose of this research was to increase the thinking ability of the sixth grade students of SDN Sidodadi I/154 through the application of problem solving methods in science learning and the obstacles encountered in the application of this method. This study used four stages, namely planning, implementation or action, observation, and the reflection stage in each cycle. The teacher activity observation data reached a percentage of 84.5% or categorized as very good. Meanwhile, student activity obtained a percentage of 84.0%. For student learning outcomes showed an increase in each cycle, namely in the first cycle the average student learning outcomes were 61.7 to 81.4 in the second cycle. Thus, the application of problem solving methods in science learning to stimulate the thinking skills of class VI students at SDN Sidodadi I/154 is said to be successful. Based on the results of this study, teachers should provide opportunities for students to have critical thinking skills such as: analyzing, comparing, predicting and formulating hypotheses. Give students opportunities for self-evaluation.